2021
DOI: 10.1111/jpn.13554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary coated granules containing garlic oil diallyl disulphide and diallyl trisulphide on performance, in vitro digestibility and gastrointestinal functionality in laying hens

Abstract: This experiment was conducted to investigate the effects of dietary supplementation with coated granules (CG) on performance, in vitro digestibility and the gastrointestinal functionality in laying hens. A total of 40 Hisex Brown laying hens (36 weeks of age) were randomly divided into five equal groups; one served as a control and the other four were actual experimental groups supplemented with 0.75, 1.5, 3 or 6 g CG per day. All the hens were fed restrictively with target feed intake of 100 g basal diet/hen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(54 reference statements)
3
1
0
Order By: Relevance
“…As previous studies found, garlic oil exhibited great antibacterial activity in vivo and vitro [40][41][42], and the activity was also verified in this study. However, unexpectedly, we found that garlic oil exhibited potent potentiation (4-to 16-fold) of the effectiveness of cefquinome against ESBL E. coli in a stable concentration (256~1024 µg/mL).…”
Section: Discussionsupporting
confidence: 87%
“…As previous studies found, garlic oil exhibited great antibacterial activity in vivo and vitro [40][41][42], and the activity was also verified in this study. However, unexpectedly, we found that garlic oil exhibited potent potentiation (4-to 16-fold) of the effectiveness of cefquinome against ESBL E. coli in a stable concentration (256~1024 µg/mL).…”
Section: Discussionsupporting
confidence: 87%
“…In laying hens, it has been reported that the dietary inclusion of EOs increases the secretion of digestive enzymes (chymotrypsin, lipase, and α-amylase) [2,24] and the digestibility of dry matter, crude protein, and ether extract [23,38]. In the present study, increased VH was observed in the duodenum, jejunum, and ileum in response to EO supplementation.…”
Section: Performancesupporting
confidence: 61%
“…Furthermore, Cheng et al [10] reported up to 18 and 20% higher serum concentrations of immunoglobulin G and interleukin-2 in laying hens supplemented with EOs. Likewise, previous studies [2,49] also detected that dietary supplementation with EOs decreased the count of bacteria Salmonella sp. and Escherichia coli in the small intestine and cecum of laying hens between 17 and 26%.…”
Section: Performancesupporting
confidence: 55%
See 1 more Smart Citation